Phase change heat transfer in an L-shape heatsink occupied with paraffin-copper metal foam - Chamkha, Ali; Veismoradi, Ali; Ghalambaz, Mohammad; Talebizadehsardari, Pouyan (Applied thermal engineering, 2020)
•The melting/solidification in a metal foam L-shape heatsink is addressed.•The heatsink is subject to a transient heat pulse.•The enthalpy-porosity approach is utilized to model the phase change heat transfer.•The finite element method with grid adaptation is used to solve the governing equations.•The using the PCM-metal foam heatsink improves the transient heat transfer. The enormous transient heating loads can be occurred in various electronic components, and hence, the thermal management of such loads is a curial task. The current research aims to address the flow and heat transfer of Phase Change Materials (PCMs) embedded in metal-foams heatsink under pulse heating conditions. The heatsink is made of an L-shape enclosure with a mounted hot element at the vertical side. The element produces a pulse heat flux while the heatsink is cooled at its top wall by an external flow. As a result, the heatsink changes the direction of heat transfer by absorbing the heat from a vertical surface and dissipating through a horizontal surface. The governing equations for the phase change flow and heat transfer of PCM in a metal foam are present and transformed into a non-dimensional form to generalize the study. The finite element method with an automatic time-step and grid adaptation is adopted as the solution method. Due to the presence of unsteady heat flux, the PCM in the heatsink experiences both of the solidification and melting phase change phenome. The outcomes show that the PCM-heatsink enhances the cooling rate of the element on the activation of the heat pulse. The heatsink provides a uniform and constant efficiency during the pulse. The higher the pulse power, the higher the heatsink efficiency. The growth of the element heat flux to fourfold and sixfold of the steady heat flux results in a heatsink efficiency of η = 1.75 and η = 2.4, respectively.